(untitled) (Eurasian Scientific Herald, 2022)
This article deals with the linguocognitive study of language units representing litho in English and Uzbek. Litota improves the meaning of words and phrases as a way of discrimination, focusing on specific events by reducing their signs. In this sense, litota is opposed to hyperbola, which is why it is also called “reverse hyperbola”. Litota is often used for ethical reasons: humility and lowering one’s achievements allow one to form a positive opinion about it.